Mechatronics : electronic control systems in mechanical and electrical engineering - Bolton, W. ([S.l.] : Prentice Hall, 2004)
The integration of electronic engineering, electrical engineering, computer technology and control engineering - mechatronics - forms a crucial part in the design, manufacture and maintenance of a wide range of engineering products and processes. This book provides a clear and comprehensive introduction to the application of electronic control systems in mechanical and electrical engineering. It gives a framework of knowledge that allows engineers and technicians to develop an interdisciplinary understanding and integrated approach to engineering.